HBV REACTIVATION AFTER HEMATOPOIETIC CELL TRANSP LANTATION IN AN HBSAB-POSITIVE RECIPIENT: ROLE OF HBV DNA QUANTITATIVE ASSAY - Hirohata, Sigeya; Nakamura, Masanori; Yasutake, Koichi; Mizuno, Ishikazu; Mito, Hisashi; Imoto, Shion; Koizumi, Tamio; Yamashita, Mariko; Hato, Akio; Murayama, Toru; Nose, Yoshisuke (Journal of the Japan Society of Blood Transfusion, 2002)
Reactivation of HBV during treatment of chronic GVHD in a recipient with positive HBs Ab. Reactivation of HBV after hematopoietic cell transplantation is a major issue of concern. A 46-year-old female with AML in 2nd CR received an allogeneic bone marrow transplantation (BMT) in September 1999. Before BMT, she was positive with HBsAb and HBcAb. She suffered from chronic GVHD six months after BMT and has been treated with prednisolone. HbsAg became positive on 22 months post-BMT. HBV DNA titer measured by PCR was 5.5log copy/ml, and was elevated to more than the upper limit of PCR (7.6log copy/ml) two months later. HBV DNA was measured by TMA-HPA (transcription mediated amplification-hybridization protection assay) thereafter. HBV DNA was elevated to 8.0log copy/ml at 28 months post-BMT, and we initiated lamivudine therapy. HBV DNA rapidly dropped to 1/100 one month later, and to 1/1000 three months later. She has remained free from liver dysfunction.